Genetic relationship between the Maoping Pb-Zn deposit and paleo-oil reservoir in the northern Yunnan-Guizhou depression: Evidence from bitumen trace elements and the in-situ sulfur isotope of pyrite associated with bitumen - Xu, Saihua; Hu, Yuzhao; Cheng, Yong; Zhu, Jizhan; Ping, Yuan; Zhang, Qimeng; Pei, Zixuan (Frontiers in Earth Science, 2023)
The coexistence of numerous Mississippi Valley-type (MVT) Pb-Zn deposits and oil/gas reservoirs in the world demonstrates that a close genetic link between them. The northern Yunnan–Guizhou depression (NYGD) is a tectonic unit containing Pb–Zn deposits, paleo-oil reservoirs and shale gas. However, previous studies on the relationship between hydrocarbon accumulation and Pb–Zn mineralization have been ignored. The Maoping Pb–Zn deposit is a large-sized MVT deposit in the NYGD where a large amount of solid bitumen (i.e., a paleo-oil reservoir) occurs, and it is an ideal area to study the relationship between hydrocarbon accumulation and lead–zinc mineralization. In this paper, the bitumen and pyrite associated with bitumen from the Xujiazhai (discovered in this study) and Xiaocaoba paleo-oil reservoirs and the Maoping Pb–Zn deposit are researched. Geological observation has revealed that bitumen occurs in dissolution pores, fractures and intercrystalline pores in dolomite of the Upper Devonian and Carboniferous. The bitumen from Xujiazhai, Maoping and Xiaocaoba with high and similar Raman equivalent reflectance (RmcRo%) indicates they are in over-mature level and may be derived from the cracking of early-accumulated crude oils. The bitumen in the Xujiazhai paleo-oil reservoir and Maoping deposit has an abundant Pb and Zn content, indicating petroleum liquids may act as the transporting agents of metallogenic metal elements, carrying them to sites where mineralization may take place. The source rocks may have provided not only the oil for paleo-oil/gas reservoirs, but also a portion of ore metals for the Pb-Zn mineralization. The bacterial sulfate reduction (BSR) and thermochemical sulfate reduction (TSR) processes were recorded by the pyrite in the paleo-oil reservoir, which was consistent with the mechanism of reduced sulfur formation in the Maoping deposit. In addition, the large negative (−27.7‰ to −5.7‰) and positive (.9‰ to 19.2‰) δ34S values of the pyrite associated with the bitumen in the paleo-oil reservoir were similar to those of the sulfide in the Maoping deposit. We believe that the formation and evolution of the paleo-oil reservoirs are closely related to the metallogenic process of the Maoping Pb–Zn deposit, and the sulfides in them have the same sulfur source and formation mechanism as reduced sulfur. BSR phenomena could occur in prior to migration of the hydrocarbons into the reservoir or low mature oil stage in paleo-oil reservoir; a small amount of H2SBSR was combined with metal ions in ancient oil reservoirs and deposits to form early subhedral, xenomorphic granular, fine-grained strawberry aggregate pyrite and/or gelatinous sphalerite. The paleo-gas reservoir formed by the evolution of the paleo-oil reservoir in the main metallogenic period potentially participated in the mineralization; that is, organic gas acted as a reducing agent and transformed SO42− in the upper Devonian Zaige Formation gypsum strata on the periphery of the Maoping lead–zinc mining area into H2STSR through TSR, providing reduced sulfur and creating the environmental conditions for mineralization. During or after the transformation of the paleo-oil reservoir to a paleo-gas reservoir, the decoupling of metals and organic complexes may have provided the ore metals for mineralization. Massive sulfide precipitation may have occurred during or after the paleo-oil reservoir cracked into the paleo-gas reservoir.